Social Space and Stage of Makassar Cultural Preservation: History of Kampung Paropo 1977-2023 - Zulkifli, Zulkifli; Ahmadin, Ahmadin; Malihu, La (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2025)
Urban villages are a topic of interest to researchers, especially in urban social, economic and cultural studies. There are many peculiarities, especially narratives about social systems and cultural heritage, which need to be dialogued in social science studies. This research examines the history of the establishment of Paropo Village in Makassar City, social and cultural development, and efforts to preserve traditional culture. As a type of qualitative historical research, the research method uses four stages, namely: heuristics, source criticism, interpretation, and historiography. The results showed that Paropo Village was founded by four figures, namely I Janggo' Cambang Paropo, Dato' Pung Malaja, and Sheikh Al-Amin, with the first three houses facing north. In 1970, the village officially became part of Makassar City after previously belonging to Gowa. Paropo Village has two types of traditional cultural preservation, namely Kondobuleng Theater and Pepe'pepekka ri Makka Dance, which are preserved by conducting natural regeneration through an art studio known as Baruga Paropo.